(untitled) (Colombia Medica, 2016)
Background:Gorham-Stout disease (GSD) is a rare disease of unknown etiology characterized by vascular proliferation that produces destruction of bone matrix. Case description:This case is about 43 year old woman who begins with pain in sternum, dyspnea, abdominal mass and, serous-hematic pleural effusion. Imaging tests were performed showing lesions on 6th and 10th left ribs archs. Later, a thoracotomy was performed observed absence of the end of the 6th and lung, pleural and costal biopsy was token. The histologic features described lymphatic vascular proliferation in bone tissue of chest wall. Other pathologies were excluded and in view of the findings, GSD diagnosis was made. Treatment and outcome:treatment was initiated with sirolimus achieving remission of the disease after the first month; however, because the presence of metrorrhagia the treatment was discontinued, reappearing symptoms afterwards. For that reason the treatment was restarted getting disappearance of the symptoms again, 4 weeks later. Clinical relevance:we present the first clinical cases of EGS with pleural effusion with response to sirolimus treatment that could be an alternative to the current therapy.